Reducing Errors in Transition from Acute Stroke Hospitalization to Inpatient Rehabilitation - Hill, Chloé E.; Varma, Priya; Lenrow, David; Price, Raymond S.; Kasner, Scott E. (Frontiers in Neurology, 2015)
Objective: Effective stroke care does not end with acute treatment during hospitalization, but extends through Objective: Effective stroke care does not end with acute treatment during hospitalization, but extends through rehabilitation and secondary stroke prevention. In transitions across care environments, stroke patients are vulnerable to errors in communication of diagnosis and treatment. This study aimed to demonstrate that formalized communication between the neurology team and the rehabilitation medicine team would promote secondary stroke prevention and minimize interruptions during rehabilitation. Methods: The intervention was a standardized verbal handoff by phone between the discharging neurology resident and the admitting rehabilitation resident regarding each patient at transfer. This retrospective cohort study compared a pre-intervention control group (September 2012- February 2013) and a post-intervention group transferred with the handoff (September 2013- January 2014). The outcomes measured included errors in communication of stroke severity, stroke mechanism, medications, and recommended follow-up (appointments and tests) as well as emergent brain imaging, return to the acute care facility, and readmission. Results: The pre- and post-intervention groups were similar with respect to number of patients (50 vs. 52) and demographics including gender (52% vs. 54% female), age (65.8 vs. 64.0 years), severity of illness as measured by the NIHSS (10 vs. 6.5), and stroke type (84% vs. 77% ischemic). Implementation of the handoff decreased errors in communication of diagnosis (NIHSS 92% vs. 74%, p=0.02; stroke mechanism 54% vs. 30%, p=0.02). Furthermore, the handoff decreased the proportion with errors in reconciliation of critical medications (42% vs. 23%, p=0.04). However, the intervention did not significantly reduce interruptions of the rehabilitation program, such as emergent brain imaging (8% vs. 12%, p=0.55) or transfers back to the acute care hospital (26% vs. 21%, p=0.56). Conclusions: Standardized handoffs decreased errors in communication of diagnosis and critical medications for secondary stroke prevention.